International legal regulation of cyber policy, cyber security, and digital conflicts: international cooperation of states - Skrypniuk, Oleksandr; Zavoritnya, Halyna; Chystiakova, Anastasiia; Komarov, Volodymyr; Kravchenko, Mykhailo; Чистякова, Анастасія Сергіївна (MAGNANIMITAS Assn., 2024)
Information can be as harmful as weapons in today's world.Cyber threats are increasing every year, making this issue more relevant than ever. Cyberattacks are chaotic activities that aim to cause harm or destruction to vital nformation. The purpose of the article is to examine the relationship between international law and cyberspace, specifically focusing on the legal aspects of cybersecurity and digital conflicts. The protection of the information space is a pressing issue that requires fruitful cooperation among leading countries worldwide. International cooperation in cybersecurity aims to find ways to protect against external threats by improving the regulatory and technical framework. It is important to note that the security situation in the world is increasingly threatened by cyber threats every year. Currently, countering cybercrime is mainly focused on improving international legal norms and balancing the legislation of leading countries in the world. The article discusses the importance of studying cybersecurity in modern cyberspace. It characterises the main concepts of the topic and reveals the content of international methods for combating cybersecurity. Emphasis is placed on the expediency of fruitful cooperation among leading countries in overcoming the negative impact of cyberattacks on infrastructure, economy, government, and security sectors. The importance of Ukraine's collaboration with major global powers in safeguarding the information space is highlighted.
Keywords: cyberattack; cybersecurity; digital conflict; Internet; international law; unauthorized actions with information; countering cyber-attacks; finance; financial security